O programa de residência multiprofissional na construção profissional de terapeutas ocupacionais : The multiprofessional residency program in the professional construction of Occupational Therapists - Peruzzolo, Dani Laura; Escouto Cunha, Talita Silveira (Revista Interinstitucional Brasileira de Terapia Ocupacional - REVISBRATO, 2025)
Introdução: A Residência Multiprofissional em Saúde se caracteriza como curso de especialização na modalidade de ensino pós-graduação lato sensu. Este oferece o Programa de Residência Multiprofissional em Atenção à Saúde da Mulher e da Criança, que acolhe residentes da Terapia Ocupacional. Objetivo: Analisar o impacto do Programa de Residência na construção profissional das Terapeutas Ocupacionais. Métodos: Estudo qualitativo, descritivo, realizado com terapeutas ocupacionais egressas desta Residência. Resultados: Quatro mulheres terapeutas ocupacionais participaram da pesquisa. Mulheres entre 25 e 30 anos que trabalharam imediatamente após o término da Residência. Duas trabalharam no sistema público de saúde. Atualmente todas encontram-se no sistema privado. Discussão: Os conhecimentos marcantes foram a importância da atenção em saúde do Sistema Único de Saúde, as habilidades para atuar multiprofissionalmente e a intervenção de terapia ocupacional com o público materno-infantil no contexto hospitalar e ambulatorial. Conclusão: A pesquisa apontou que houve impacto muito positivo do Programa de Residência na construção profissional das egressas e que, mesmo não estando atuando no sistema público de saúde, conseguem utilizar os princípios do Sistema Único de Saúde em sua prática. A Terapia Ocupacional, ao passo que se insere nas RMS, tem validado sua prática e se fortalecido como profissão. Abstract: Introduction: The Multiprofessional Residency in Health is characterized as a specialization course in the lato sensu post-graduation teaching modality. It includes the Multiprofessional Residency Program in Women's and Children's Health Care, which includes residents of Occupational Therapy. Aims to analyze the impact of this Residency Program on the professional development of Occupational Therapists. Methods: A descriptive, qualitative study, carried out with occupational therapists who had graduated from this Residency. Results: Four female occupational therapists between 25 and 36 years old participated. All worked immediately after the residency. Two went on to work in the public health system. Currently all of them are in the private system. Discussion: The outstanding knowledge was the importance of health care in the Unified Health System, the skills to act multiprofessionally and the occupational therapy intervention with the mother-child public in hospital and outpatient settings. Conclusion: The research showed that there was a very positive impact of the Residency Program on the professional construction of the graduates, in which the professionals acquired significant knowledge regarding the Unified Health System, multidisciplinary team work and occupational therapy interventions with the maternal and child public, which they still use in their current practice. Multiprofessional residency continues to be an excellent qualification space for the Unified Health System, where Occupational Therapy is strengthened as a profession. Keywords: Occupational Therapy. Continuing education. Maternal and Child Health